Factors influencing the approach to community development in Ghanaian urban slums. Issue 3 (27th May 2022) - Frimpong-Manso, Kwabena; Appiah-Kubi, Jamal
ABSTRACT: The approaches used in community development (CD) are critical to the success or failure of projects. Yet, we know little about approaches employed in CD in urban areas. This study investigates the approaches employed in two CD projects (construction of footbridges and cassava processing) in Ashaiman, an urban Ghanaian slum, and the factors that influenced the selected approaches. We used a qualitative technique by conducting semi-structured interviews with 23 stakeholders involved in CD activities in Ashaiman. Interviews were audio-recorded, transcribed, and thematically analyzed. The findings demonstrated that the two selected initiatives used both self-help and technical support approaches, with the latter approach dominating. The community's capacity, weak social ties among the residents, and nature of the project undertaken were the factors that determined the approaches taken. The basis for the approach used in CD should be the characteristics of the communities and how they facilitate the successful implementation of projects.